Structural performance of buildings during the 30 November 2018 M7.1 Anchorage, Alaska earthquake. Issue 1 (February 2022) - Hassan, Wael M; Rodgers, Janise; Motter, Christopher; Thornley, John
Southcentral Alaska, the most populous region in Alaska, was violently shaken by a Mw 7.1 earthquake on 30 November 2018 at 8:29 am Alaska Standard Time. This was the largest magnitude earthquake in the United States close to a population center in over 50 years. The earthquake was 46 km deep, and the epicenter was 12 km north of Anchorage and 19 km west of Eagle River. The event affected some 400, 000 residents, causing widespread damage in highways, nonstructural components, non-engineered and older buildings, and structures on poorly compacted fills. A few isolated serious injuries and partial collapses took place. Minor structural damage to code-conforming buildings was observed. A significant percentage of the structural damage was due to geotechnical failures. Building stock diversity allows use of the region as a large test bed to observe how local building practices affected earthquake damage levels. The prevailing peak ground acceleration (PGA) was 0.2–0.32 g, causing shaking intensity at most sites of 50%–60% of the ASCE 7-16 design basis earthquake acceleration. Thus, the seismic vulnerability of building stock in the region was not truly tested. Reinforced concrete buildings had minor structural damage, except in a few cases of shear wall and transfer girder shear cracking. Fiber-reinforced polymer (FRP)-retrofitted buildings performed satisfactorily. Concrete-masonry-unit (CMU) masonry buildings experienced serious structural damage in many cases, including relatively newer buildings. The earthquake caused widespread structural damage in non-engineered buildings (primarily wood and CMU masonry) that exist widely in the region, especially in Eagle River. Of these, non-engineered single-family wood buildings had the heaviest structural damage. No structural damage could be observed in steel buildings. The aftershock sequence, which included 7 M5+ and 50 M4+ events, exacerbated structural damage in all types of buildings. The present study is based on the EERI field reconnaissance mission conducted by the authors following the earthquake. Based on the observed damage and structural performance, seismic risk mitigation recommendations are suggested.